Historical Memory of Ainu through Material Culture in Japanese Literary Text: An Analysis of Tsushima Yuko’s Work - Wawat Rahwati; Budi Mulyadi; Andres Suhendrawan (Universitas Diponegoro, 2021)
This research discusses the elements of material culture in the literary text of Jakka Dofuni Umi no Kioku no Monogatari by Tsushima Yuko in presenting historical memories of the Ainu as one of the indigenous people in Japan. Material culture is a study carried out through objects (artefacts) to see social markers, historical traces, social knowledge, and the identity of a particular nation or society. This research aims to reveal the history and identity of the Ainu as shown through material cultural objects and how the characters in the text interpret these objects. Qualitative approaches and narrative structures as research methods are used to analyze this literary text. Besides, memory theory is also used to reveal collective memories related to Ainu history and identity. The results show that the Jakka Dofuni museum with various artefacts presents historical memory and Ainu identity through the narrator's discussion and figures in narratives text. The spirit consolation monument (ireihi), which was built in the area of the Jakka Dofuni museum, is an object of memory of remembrance for local people from the Ainu and Uilta tribes who were victims of war during the Russo-Japanese War (1904-1945). The collection of cultural artefacts and the life history of Gendanu as the owner of the museum with the identity problems he experienced can be interpreted as a form of markers that confirm Ainu's identity.